2021
DOI: 10.1124/pharmrev.120.000046
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic Potential of Terpenes Derived fromCannabis sativa

Abstract: Pain prevalence among adults in the United States has increased 25% over the past two decades, resulting in high health-care costs and impacts to patient quality of life. In the last 30 years, our understanding of pain circuits and (intra)cellular mechanisms has grown exponentially, but this understanding has not yet resulted in improved therapies. Options for pain management are limited. Many analgesics have poor efficacy and are accompanied by severe side effects such as addiction, resulting in a devastating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 283 publications
(659 reference statements)
0
46
0
Order By: Relevance
“…In addition to phytocannabinoids, the Cannabis genus also produces non-cannabinoid compounds, including terpenoids ( 12 ), which may also be medically useful ( 13 15 ). The pharmacological contributions of minor cannabinoids and non-cannabinoid compounds have been highlighted and popularized under the term “entourage effect” ( 16 , 17 ).…”
Section: Cannabis a Square Peg In The Round Hole Of Evidence-based Me...mentioning
confidence: 99%
“…In addition to phytocannabinoids, the Cannabis genus also produces non-cannabinoid compounds, including terpenoids ( 12 ), which may also be medically useful ( 13 15 ). The pharmacological contributions of minor cannabinoids and non-cannabinoid compounds have been highlighted and popularized under the term “entourage effect” ( 16 , 17 ).…”
Section: Cannabis a Square Peg In The Round Hole Of Evidence-based Me...mentioning
confidence: 99%
“…Among the several components of Cannabis Sativa, as flavonoids, vitamins, fatty acids, sterols, lignanamides, spiroindans, and alkaloids that may have health benefits [ 21 ], terpenes represent a very attractive option for pain treatment [ 22 ]. In particular, β-caryophyllene (BCP), a bicyclic sesquiterpene very present in Cannabis Sativa, has been widely investigated and highly appreciated for its low toxicity and considerable safety profile [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to being found in hops, thyme, and bay leaves, myrcene is the most prevalent monoterpene in Cannabis . In preclinical studies, administration of essential oils rich in myrcene have been found to have analgesic and anti-inflammatory properties [ 2 , 3 ]. Eremanthus erythropappus (10% myrcene) and Bougainvillea glabra (4% myrcene) increased hindpaw withdrawal time in mice and rats in response to noxious heat while reducing paw licking in mice injected with formalin [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In joints, cannabinoid receptor activation locally can alter synovial blood flow, leukocyte trafficking, and joint oedema [ 17 , 18 , 19 , 20 ]. Since some terpenes can act directly on cannabinoid receptors and alter the pharmacokinetics of phytocannabinoids [ 3 , 21 ], the interaction between terpenes and the endocannabinoid system warrants further investigation.…”
Section: Introductionmentioning
confidence: 99%